2020
DOI: 10.1108/ejim-01-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

Cultural intelligence and innovative work behavior: the role of work engagement and interpersonal trust

Abstract: PurposeBecause of the rapidly changing environment and fleeting market opportunities, employee's innovative work behavior is increasingly assuming a pivotal role in enhancing organizational effectiveness and competitive advantage. The success of organizations is largely depended on their employees' ability to innovate. The role of cultural intelligence to enhance innovative work behavior is yet to be explored in the innovation research. The purpose of this study is to examine how cultural intelligence enhances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
132
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(144 citation statements)
references
References 98 publications
(154 reference statements)
10
132
0
2
Order By: Relevance
“…Employees with high engagement have a more positive attitude towards their work and organization, pay more respect to their colleagues, help others heighten the work efficiency, improve their own work skills, and perform at a very active state, which contributes to improving the performance of their in-role and extra-role behaviors [ 67 ]. Lyu et al [ 69 ] and Afsar et al [ 70 ] have confirmed the opinion, which also shows that there is a positive association between engagement, organizational citizenship behavior and innovative work behavior.…”
Section: Theoretical Backgroundmentioning
confidence: 75%
“…Employees with high engagement have a more positive attitude towards their work and organization, pay more respect to their colleagues, help others heighten the work efficiency, improve their own work skills, and perform at a very active state, which contributes to improving the performance of their in-role and extra-role behaviors [ 67 ]. Lyu et al [ 69 ] and Afsar et al [ 70 ] have confirmed the opinion, which also shows that there is a positive association between engagement, organizational citizenship behavior and innovative work behavior.…”
Section: Theoretical Backgroundmentioning
confidence: 75%
“…A recent longitudinal pilot study also confirmed that CQ training can improve individual innovative work behavior ( Azevedo and Shane, 2019 ). Afsar et al (in press) also found that CQ could influence individual’s innovative behavior significantly. In this study, we argue that high CQ could bring migrant workers the informational and effective support from colleagues, which is of immense significance and essential for the migrant workers to accomplish challenging tasks, develop novel ideas, and adopt innovative behavior in a culturally diverse workplace ( Madjar, 2008 ).…”
Section: Introductionmentioning
confidence: 86%
“…Particularly, in a diverse workplace comprising members of different cultures, the capability of interacting effectively becomes extremely important to acquiring information and important resources from each other. On the one hand, employees with higher CQ have a stronger motivation to communicate frequently and effectively with the colleagues from different cultural backgrounds, which could elevate an employee’s central position in the social context, consequently enabling them to acquire diverse information from others ( Chen et al, 2008 ; Afsar et al, in press ). Additionally, communicating with colleagues frequently and effectively can also facilitate members to reach consensus on task-related issues, enhance sharing of critical information, and enable the employee’s acquisition of high-quality information ( Chen et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations